Математико-механическая модель разрушения пород при бурении - Горшков, Л.К.; Яковлев, А.А.; Павлов, Н.А. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2010)
Rock failure mechanism in the process of drilling may be defined as oscillating process described
by difference-differential equation which goes with equation for torque factor which is
transmitted to the string through robust transmission from pumping power. In this case specific
drag torque to rotating of drilling assembly is a cubic dependence from angular rate of rotation.
The model is verified experimentally and is acknowledged as practically adaptable.